Optimization of Vacuum Impregnation with Aqueous Extract from Hibiscus sabdariffa Calyces in Apple Slices by Response Surface Methodology: Effect on Soluble Phenols, Flavonoids, Antioxidant Activity, and Physicochemical Parameters - Luis Miguel Anaya-Esparza; Ernesto Rodríguez-Lafitte; Zuamí Villagrán; Edward F. Aurora-Vigo; José Martín Ruvalcaba-Gómez; Walter Bernardo Símpalo-López; Fernando Martínez-Esquivias; Cristhian Henry Sarango-Córdova (Applied Sciences)
Vacuum impregnation (VI) of natural extracts is often used as a pretreatment for fruit dehydration. Apple slices were subjected to VI [XVP: vacuum pressure (−0.4 to −0.2 mbar), XIT: impregnation time (2–10 min), and XRT: restoration time (1–3 min)] of Hibiscus sabdariffa (HS) calyces aqueous extract and optimized using response surface methodology (RSM). Total soluble phenols (TSP) and flavonoids, antioxidant capacity, and physicochemical parameters were evaluated before and after vacuum impregnation. Also, optimized VI apple slices were heat air-dried and characterized for all the mentioned parameters. Under the experimental conditions, all vacuum-impregnated apple slices increased in TSP content, with impregnation time, restoration time, and the interaction between impregnation time and vacuum pressure being the key factors. According to RSM, the optimal VI conditions for TSP (R2 = 0.99) were XVP −0.4 bar, XIT: 6.73 min, and XRT 3 min. VI also improved flavonoid and antioxidant activities (DPPH and ABTS) of apple slices and promoted changes in total soluble solids, pH, titratable acidity, water activity, moisture, and color (luminosity, a*, and b*) parameters. Additionally, vacuum-impregnated apple slices (under optimized conditions) were further dehydrated, resulting in an increase in soluble phenols, flavonoids, and antioxidant activity. VI with HS extract is an effective alternative for developing dehydrated apple slices with an increase in antioxidant compounds.